(3efGRd GdbeQs - (3YHO GdQMef Hf YjSi Hf GdYeQGfjs ((3eMeO Hf eMeO GdNGdOi GdhOZjQi GdMSfi s)
(3ChdgG (B:s
(3GdMeO ddg ebOQ GdbeQ efGRdg JHUQI djYJHQ SHMGfg ef YGde Mcje eRjf GdCadGc HGdfLhe s
(3BNQgG (B:s
(3eLehYgG hGWQM dcd efRdg jhejkG Yf GdeLehYI hGLYd Chdg ef WGdY HGdaLQ jhe aMjK jfJgi jcf ebhdg JeJ GdefXheI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs